(untitled) (Fiep Bulletin - online, 2015)
This study aimed to reunite information concerning backbone lesions in tennis players, pointing out main aspects, such as, causes, types of lesions, diagnostic and prevention. Methods and techniques of bibliographic research were used in its realization based on articles published in scientific journals, magazines, books, congresses records, Internet articles and thesis texts. The main causes of lesions caused by tennis overload are due to inadequate training structure in relation to type, frequency, intensity and duration of the sessions. The service is considered to be the main cause of backaches in tennis players due to the high physical demand used during the stroke. The backbone, as well as the pelvis and the shoulders are the most sensible regions affected by the overload originated from exaggerated rotations and torsions. Postural and anthropometric evaluations need to be regularly done as to control the level of deviation in the backbone and the members’ asymmetry, especially in young tennis players still in body formation age. The biomechanical analysis of technical gestures, still little used by professionals, may be implemented, becoming an essential tool in prevention of backbone lesions.